KAJIAN ETNOLINGUISTIK PADA KULINER KHAS KABUPATEN GRESIK SEBAGAI REPRESENTASI IDENTITAS BUDAYA LOKAL - Atikoh, Iklilah (Department of Master of Linguistic, Universitas Airlangga, 2025)
Abstract: : This study aims to explore the relationship between language, culture, and local identity through the ethnolinguistic analysis of traditional Gresik cuisine. A total of 14 culinary names were documented, including Sego Krawu, Pudak, Mangut Bandeng, and Otak-Otak Bandeng, which serve as a medium for communicating cultural values passed down through generations. Data were collected through in-depth interviews with local residents, direct observations, and literature reviews, and analyzed using a qualitative descriptive method. The findings reveal that the names of traditional Gresik dishes reflect the region's historical significance as a port city, its social and cultural traditions, and its close connection with the geographic environment. For instance, the term “Pudak” illustrates the community's creativity in utilizing natural materials such as areca palm leaves as wrappers, while “Sego Krawu” symbolizes the simplicity and togetherness of the people. Additionally, the influence of the historical spice trade is evident in cooking techniques such as salting and the use of rich spices in dishes like Mangut Bandeng. Culinary names also serve as markers of cultural identity, strengthening the community's sense of belonging. In the context of globalization, these names symbolize resistance to culturalhomogenization. Through food festivals, they play a role in cultural diplomacy, introducing Gresik's unique heritage to the broader world. This documentation aims to preserve culinary traditions as intangible cultural heritage and provides a reference for future linguistic and anthropological studies. Keywords: ethnolinguistics, traditional Gresik cuisine, cultural preservation.